THE DISTINCTIVE FEATURES OF AUSTRALIAN ENGLISH - Bokieva Muharramoy Ne'matjon kizi (TADQIQOTLAR, 2025)
Australian English (AusE) represents a unique variant of the English language, shaped  by  historical,  cultural,  and  social  influences.  This  study  examines  the phonological,  lexical,  and  syntactic  characteristics  of  AusE,  highlighting  its distinctiveness from other English varieties. Through a systematic review of linguistic data and sociolinguistic analysis, the research identifies key features such as vowel shifts, unique vocabulary, and informal syntactic structures. The findings underscore AusE's  role  as  a  dynamic  and  evolving  dialect,  reflecting  Australia's  multicultural identity.